Characterizing conflict and congruence of molecular evolution across organellar genome sequences for phylogenetics in land plants - Tyszka, Alexa S.; Bretz, Eric C.; Robertson, Holly M.; Woodcock-Girard, Miles D.; Ramanauskas, Karolis; Larson, Drew A.; Stull, Gregory W.; Walker, Joseph F. (Frontiers in Plant Science, 2023)
Chloroplasts and mitochondria each contain their own genomes, which have historically been and continue to be important sources of information for inferring the phylogenetic relationships among land plants. The organelles are predominantly inherited from the same parent, and therefore should exhibit phylogenetic concordance. In this study, we examine the mitochondrion and chloroplast genomes of 226 land plants to infer the degree of similarity between the organelles’ evolutionary histories. Our results show largely concordant topologies are inferred between the organelles, aside from four well-supported conflicting relationships that warrant further investigation. Despite broad patterns of topological concordance, our findings suggest that the chloroplast and mitochondrial genomes evolved with significant differences in molecular evolution. The differences result in the genes from the chloroplast and the mitochondrion preferentially clustering with other genes from their respective organelles by a program that automates selection of evolutionary model partitions for sequence alignments. Further investigation showed that changes in compositional heterogeneity are not always uniform across divergences in the land plant tree of life. These results indicate that although the chloroplast and mitochondrial genomes have coexisted for over 1 billion years, phylogenetically, they are still evolving sufficiently independently to warrant separate models of evolution. As genome sequencing becomes more accessible, research into these organelles’ evolution will continue revealing insight into the ancient cellular events that shaped not only their history, but the history of plants as a whole.